Cytochrome P450‐catalyzed biosynthesis of furanoditerpenoids in the bioenergy crop switchgrass (Panicum virgatum L.). (24th September 2021) - Muchlinski, Andrew; Jia, Meirong; Tiedge, Kira; Fell, Jason S.; Pelot, Kyle A.; Chew, Lisl; Davisson, Danielle; Chen, Yuxuan; Siegel, Justin; Lovell, John T.; Zerbe, Philipp
SUMMARY: Specialized diterpenoid metabolites are important mediators of plant–environment interactions in monocot crops. To understand metabolite functions in plant environmental adaptation that ultimately can enable crop improvement strategies, a deeper knowledge of the underlying species‐specific biosynthetic pathways is required. Here, we report the genomics‐enabled discovery of five cytochrome P450 monooxygenases (CYP71Z25–CYP71Z29) that form previously unknown furanoditerpenoids in the monocot bioenergy crop Panicum virgatum (switchgrass). Combinatorial pathway reconstruction showed that CYP71Z25–CYP71Z29 catalyze furan ring addition directly to primary diterpene alcohol intermediates derived from distinct class II diterpene synthase products. Transcriptional co‐expression patterns and the presence of select diterpenoids in switchgrass roots support the occurrence of P450‐derived furanoditerpenoids in planta . Integrating molecular dynamics, structural analysis and targeted mutagenesis identified active site determinants that contribute to the distinct catalytic specificities underlying the broad substrate promiscuity of CYP71Z25–CYP71Z29 for native and non‐native diterpenoids. Significance Statement: Cytochrome P450 monooxygenases catalyze the various functional decorations of core diterpene scaffolds that determine the large diversity of biologically active plant diterpenoids. This study describes the identification, structure–function analysis and gene expression analysis of a group of cytochrome P450 monooxygenases, CYP71Z25–CYP71Z29, from the bioenergy crop switchgrass ( Panicum virgatum ). CYP71Z25–CYP71Z29 catalyze the addition of a furan ring to primary alcohol derivatives of class II diterpene synthase products.